Adherence to ESC cardiac resynchronization therapy guidelines: findings from the ESC CRT Survey II. Issue 6 (24th April 2020) - Normand, Camilla; Linde, Cecilia; Blomström-Lundqvist, Carina; Stellbrink, Christoph; Gasparini, Maurizio; Anker, Stefan D; Plummer, Chris; Sarigul, Nedim Umutay; Papiashvili, Giorgi; Iovev, Svetoslav; Dickstein, Kenneth
Abstract: Aims: Cardiac resynchronization therapy (CRT) reduces morbidity and mortality in patients with heart failure (HF) and electrical dyssynchrony. The European Society of Cardiology (ESC) Guidelines provide evidence-based recommendations indicating optimal patient selection for CRT implantation in both the 2013 European Heart Rhythm Association (EHRA) and the 2016 Heart Failure Association (HFA) Guidelines. We assessed the adherence to guidelines and identified factors associated with guideline adherence. Methods and results: In 2016, the HFA and EHRA conducted the CRT Survey II in 42 ESC countries. The data collected were sufficient to evaluate adherence to guidelines in 8021 patients. Of these, 67% had a Class I guideline indication for CRT implantation, which was significantly correlated with female gender (1.70, P  < 0.0001), age <75 years (1.55, P  < 0.0001), non-ischaemic HF aetiology (1.22, P  < 0.0001), and elective admission (1.87, P  < 0.0001). A further 26% of implants had a Class IIa indication, 5% IIb and only 2% a contraindication to CRT—a Class III indication. Patients implanted under Level IIa indications were much more likely to have more comorbidities than patients implanted under Level I indications. However, there were large variations in guideline adherence between ESC countries. Conclusion: Implanters in ESC member states demonstrate a high degree of adherence to ESC guidelines with 98% of implants having a documented Class I, IIa or IIb indication. Cardiac resynchronization therapy implantation without a Class I indication was more likely in men, patients age ≥75 years, with HF of ischaemic origin and in patients admitted to hospital acutely.